2003
DOI: 10.1097/00000421-200306000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Irinotecan has shown activity in advanced colorectal cancer resistant to leucovorin and fluorouracil. Preclinical experiments on cell cultures and human tumor xenografts indicated potential synergy when combining irinotecan and fluorouracil. We designed a new regimen combining leucovorin, fluorouracil, irinotecan, and hydroxyurea (FOLFIRI-2) and conducted a phase II study to establish its efficacy and tolerance in advanced colorectal cancer refractory to fluorouracil and oxaliplatin. Treatment was repeated eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the irinotecan pre-exposed population, patients received FOLFIRI3-aflibercept as salvage therapy. Yet, median PFS and OS were 5.7 mo and 14.3 mo, respectively, and were comparable to figures observed in second-line trials[ 8 , 15 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the irinotecan pre-exposed population, patients received FOLFIRI3-aflibercept as salvage therapy. Yet, median PFS and OS were 5.7 mo and 14.3 mo, respectively, and were comparable to figures observed in second-line trials[ 8 , 15 ].…”
Section: Discussionsupporting
confidence: 83%
“…Standard second-line therapy in patients with previously treated metastatic colorectal cancer (mCRC) is doublet fluoropyrimidine-based chemotherapy with either irinotecan (FOLFIRI) or oxaliplatin (FOLFOX), depending on the regimen used in first-line, in association with antiangiogenic agents ( e.g ., bevacizumab, aflibercept, ramucirumab) or anti-EGFR agents in absence of RAS tumor gene mutation ( e.g ., cetuximab, panitumumab)[ 1 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with the above hypothesis, several studies showed that a delayed administration of irinotecan increases FOLFIRI cytotoxicity. FOLFIRI2 regimen (irinotecan delivery at the end of a modified LV5FU2 chemotherapy) in heavily pretreated CRC patients induced promising objective responses but also a limiting hematologic toxicity [19]. As reported here and in previous studies, FOLFIRI3 has a more appropriate toxicity profile [12].…”
Section: Discussionmentioning
confidence: 76%
“…60%. [ 26 ] Seventeen percent objective responses were observed in Mabro's study for FOLFIRI regimen,[ 27 ] and other studies reported response rate for FOLFIRI regimen as followed; Douillard et al . 40.8%,[ 28 ] Tourniguand et al .…”
Section: Discussionmentioning
confidence: 99%